The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fgene.2021.655707
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Data for Reliable SNP Detection and Genotype Calling: Interest for Coding Variant Characterization and Cis-Regulation Analysis by Allele-Specific Expression in Livestock Species

Abstract: In addition to their common usages to study gene expression, RNA-seq data accumulated over the last 10 years are a yet-unexploited resource of SNPs in numerous individuals from different populations. SNP detection by RNA-seq is particularly interesting for livestock species since whole genome sequencing is expensive and exome sequencing tools are unavailable. These SNPs detected in expressed regions can be used to characterize variants affecting protein functions, and to study cis-regulated genes by analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 70 publications
0
31
0
Order By: Relevance
“…Therefore, we reasoned that patient genotyping from mRNA could better reflect the ACE2 variants expressed in those patients. In fact, previous studies have shown that SNPs could be detected with high precision in transcriptome sequencing approaches as compared to DNA-seq procedures (58, 59). This has led to the emergence of transcriptome or RNA sequencing as a potential alternative approach to variant detection within protein coding regions, since the transcriptome of a given tissue represents a quasi-complete set of transcribed genes (mRNAs) and other noncoding RNAs which also bypasses the need for exome enrichment (60, 61).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we reasoned that patient genotyping from mRNA could better reflect the ACE2 variants expressed in those patients. In fact, previous studies have shown that SNPs could be detected with high precision in transcriptome sequencing approaches as compared to DNA-seq procedures (58, 59). This has led to the emergence of transcriptome or RNA sequencing as a potential alternative approach to variant detection within protein coding regions, since the transcriptome of a given tissue represents a quasi-complete set of transcribed genes (mRNAs) and other noncoding RNAs which also bypasses the need for exome enrichment (60, 61).…”
Section: Discussionmentioning
confidence: 99%
“…Data generated have been deposited in NCBI database: PRJNA766745. The male and female gonad RNAseq data from previous reports include E4.5 and E6 RNA-seq: PRJNA171809 [ 29 ], E10, E12 and E14 RNA-seq: PRJEB26695 [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 3,276,615 SNPs analyzed in this study have been detected following the method presented in the companion paper (Jehl et al, 2021) using 767 multi-tissue RNA-seq of 382 birds from 11 chicken populations (see Additional File 1). This SNP set corresponds to the union of the SNPs with reliable genotypes found in each population (list available on http://www.…”
Section: Snp Datasetmentioning
confidence: 99%
“…Using 3.3M SNPs previously detected from 767 multi-tissue RNA-seq of 382 animals from 11 chicken populations and therefore enriched in coding regions [see the companion paper (Jehl et al, 2021), section "Materials and Methods"], we identified 260,919 unique SNPs in 26,702 transcripts corresponding to 15,835 genes out of 19,545 protein-coding genes (Figure 2, right part-in yellow).…”
Section: Read-based Phasing For Identification Of Mnvsmentioning
confidence: 99%
See 1 more Smart Citation